The Role of Supply Chain Management in External Indebtedness and Its Problems in Iraq Economy - Mohammed Al-Mehannah, Hind Ghanim (International Journal of Supply Chain Management, 2019)
With rapid economic development, related social issues have become more prominent than before. How to effectively encourage enterprises to undertake more corporate social responsibility and maintain the sustainable development of society has become an urgent task for managers and researchers to resolve. With respect to decision problems of a retailer-dominated supply chain considering external indebtedness problem under government subsidy, based on game analysis technology, we consider a three-stage Stackelberg game model that consists of the government, a dominant retailer and n suppliers. In spite of the fact that the Iraqi economy is featured by its diverse resources, Iraq is suffering from external indebtedness as a result of incorrect economical policies that have led to increasing the governmental huge spending coincided with fall in governmental revenues, whose sources might be oil export, taxes, or fees, as well as sluggish development. This is as far as the domestic funding of governmental spending, which has created a huge governmental debt on one hand. In addition to that, the wars that Iraq went through and the economic sanctions have led to exacerbate the external indebtedness issue. All of that has resulted in debt accumulation and the incapability of Iraq to repay the debt service. Thus, efficient supply chain management is required for the economy in Iraq to prevent its eruption.